Studi Evaluasi Implementasi SDGs: Dalam Kurikulum Merdeka Di Sekolah Menengah Pertama - Salsabila, Salwa Azahra Putri; Nabilah, Fina; Rachman, Ichsan Fauzi (Jurnal Literasi dan Pembelajaran Indonesia, 2025)
This study aims to evaluate the extent to which the implementation of the 17 Sustainable Development Goals (SDGs) has been integrated in the Merdeka Curriculum at the Junior High School (SMP) level. Using a literature study approach, this research analyzes various relevant and credible literature sources. The results of the study show that the Merdeka Curriculum has significant potential in accommodating the values of the SDGs through a project-based, contextual, and learner-centered learning approach. However, this integration still faces a number of challenges, such as limited teacher understanding, lack of supporting resources, and lack of specific policies that direct the strengthening of SDGs in learning practices. Therefore, cross-sectoral support is needed to ensure the sustainability and effectiveness of SDGs integration in schools. This research is expected to be an initial reference for the development of more sustainability-oriented education policies.